Alumni Leadership and University Excellence in Africa The Case of Lagos Business School - Onukwuba, Henry O. (Palgrave Studies in African Leadership, 2018)
'This is a book that I strongly recommend to all those who wish to attain an in-depth practical understanding of how to start, structure and govern alumni associations of all kinds.' -Juan Elegido, Vice Chancellor and Professor, Pan-Atlantic University 'Borne out of practical experience, this is a well thought-out book for educational institutions looking to establish a lasting legacy through the formation of a viral and strong alumni association.' -Wole Oshin, Group Managing Director, Custodian & Allied Plc and Past President, LBS Alumni Association Focusing on Lagos Business School (LBS) in Nigeria, this book explores the impact of strong alumni leadership on university excellence in Africa. Strong leadership is crucial to the success of educational institutions and great importance is placed on their effective governance and management. However, many institutions fail to realise the positive impact that a strong alumni body can have on university excellence. Drawing on definitions and theories of leadership, the author seeks to establish the significance of alumni in enhancing a university's growth and development. Providing comprehensive analysis of LBS, this book is a unique resource for leaders of educational institutions, as well as those studying and teaching in African business schools.